The Management of Psychiatric Emergencies in Situations of Public Calamity - Baldaçara, Leonardo; da Silva, Antônio Geraldo; Pereira, Lucas Alves; Malloy-Diniz, Leandro; Tung, Teng Chei (Frontiers in Psychiatry, 2021)
The prevalence of mental health problems in the general population during a public calamity is high. In calamities, the number of patients who present with mental disorder outbreaks or crises may increase, but the necessary support systems to help them may be impaired if they have not been planned for. Although there are several models for addressing psychiatric emergencies, the general rules are the same, especially when it comes to making these services easily available to the affected population. In this article, we seek to review and present recommendations for the management of psychiatric emergencies in situations of public calamity, including disasters, physical and medical catastrophes, epidemics, and pandemics.